Pengendalian Persediaan Bahan Baku Jamur Tiram di UD Khalifa Jamur dengan EOQ - Koko Hermanto; Moch lahmudin; Ismi Mashabai; Ulfa Turrahmi (UJMC (Unisda Journal of Mathematics and Computer Science), 2026)
Khalifa Mushroom is one of the oyster mushroom cultivation places, the company is advised to start implementing the EOQ method consistently in the planning and inventory process of raw materials. This is important so that the amount of production processing and ordering time can be adjusted to actual needs and dynamic market conditions. Second, the company should utilize technology optimally to perform calculations and inventory control simulations to produce fast, accurate, and efficient decisions. This study to anticipate increased production volume, the company is advised to always apply the Economic Order Quantity (EOQ) method to evaluate existing warehouse capacity and consider expanding or rearranging storage space so that raw materials maintain their quality and are not damaged due to accumulation. Finally, the researcher suggests that further research can explore the use of other methods that are integrated with supply risks, price changes, or demand fluctuations to strengthen supply chain resilience and increase business competitiveness in the future